Implementasi Inovasi Keperawatan “Therapeutic Atmosphere” di Ruang Rawat Inap - Litaqia, Wulida; Hidayati, Laili Nur (Citra Delima Scientific journal of Citra Internasional Institute, 2022)
Hospitalization for patients with mental disorders is a situation where they are far from their usual environment and live together with new and foreign people. These psychiatric disorders can cause serious psycho-social limitations for patients. The decline in social functioning is one of these limitations. Patients often experience deterioration in social functioning and self-care. Therapeutic atmosphere is designed to train the fulfillment of social needs and patient self-care. This activity aims to improve interaction skills, fulfill the patient's self-care and spiritual needs in the inpatient room. Activities in a therapeutic atmosphere include morning meetings, clean Fridays, and religious time with their respective goals and assessed using pre and post observations with indicators- indicators that have been made according to the implementation objectives. The results of the activity showed that interaction skills increased from 30% to 90%, self-care fulfillment improved and increased from 20% to 90%, and spiritual fulfillment became better from 50% to 70%. Based on these results, it is hoped that therapeutic atmosphere innovation activities can become recommendations for routine activities that are therapeutic or healing and can be applied in mental hospitals.